2004
DOI: 10.1897/03-286
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of estrogenic activity in sewage treatment plant effluents involving three in vitro assays and chemical analysis of steroids

Abstract: In this study, we assessed and compared the suitability of three in vitro screening tools for the measurement of estrogenic activity in sewage treatment plant effluents (STPEs). These assays were the yeast estrogen screen (YES), production of zona radiata proteins (ZRPs) in trout hepatocytes, and the induction of reporter gene expression in the transfected rainbow trout gonad cell line RTG-2. Data obtained with the YES were additionally compared with calculated estrogenicity, based on steroid analysis data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
79
1
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(99 citation statements)
references
References 61 publications
14
79
1
5
Order By: Relevance
“…Rutishauser et al (2004) showed that in-vitro tests were able to detect oestrogenic effects in effluents from these compounds and bisphenol A. An assessment of oestrogen removal efficiency for WTW in the UK (Johnson et al, 2007b) showed simple biological plants to be poor with only about 30% removal.…”
Section: Wastewater Treatmentmentioning
confidence: 99%
“…Rutishauser et al (2004) showed that in-vitro tests were able to detect oestrogenic effects in effluents from these compounds and bisphenol A. An assessment of oestrogen removal efficiency for WTW in the UK (Johnson et al, 2007b) showed simple biological plants to be poor with only about 30% removal.…”
Section: Wastewater Treatmentmentioning
confidence: 99%
“…Assay procedure and data analysis were conducted as described previously (Routledge and Sumpter 1996;Rutishauser et al 2004), with several modifications to test water samples directly and to accelerate the sample throughput. Minimal medium was prepared by supplementing ultrapure water with 0.67% w/v yeast nitrogen base without amino acids, 2% w/v D-(+)-glucose, and the appropriate amino acids.…”
Section: Yeast Estrogen Screenmentioning
confidence: 99%
“…Samples were enrichedbymeansofsolid-phaseextraction (SPE) and the extract was analyzed in the YES, a yeast-based reporter gene assay. [11] The estrogenic activity of the samples was expressed as 17β -estradiol equivalents (EEQs, in ng/l); [18] 17β -estradiol being the standard in the YES. As expected, EEQs in river water were higher downstream from the effluent discharge compared to the paired sample taken upstream.…”
Section: Study I: Variability Of Estrogenic Activity In Many Independentmentioning
confidence: 99%